Plataformas digitales y construcción de microemprendimientos - Meza Aviles, Ginger Anyeline (2024)
The research developed under the topic digital platforms and construction of micro-enterprises, aims to analyze the use of digital platforms in the dissemination of new ventures in the Palenque canton - province of Los Ríos, between the years 2021 - 2023 and its impact on the economy. . From this, we closely explore how entrepreneurs in this area have integrated digital platforms into their advertising communication strategies, in addition to the tools used to design content aimed at capturing the public's attention, resorting to a methodology of qualitative approach, with an exploratory scope. For data collection, convenience sampling was applied, deciding to interview three experts in the area of communication and digital business, in addition to selecting four businesses in the canton whose owners were also interviewed, obtaining data that was complemented with a form. of observation to the businesses evaluated. The results showed that the digital platforms that have the greatest use are social networks such as Facebook, Instagram and Tik-Tok, including the WhatsApp messaging platform, using tools such as Canva, Cap Cut, inShot, among others to design content related to photos and videos that are disseminated to capture the public's attention and motivate sales of the businesses in the Palenque canton, promoting their economic growth, which in turn generates an impact on the canton's economy, generating employment and contributing to the economic wellbeing of others. people linked to the business.